RELATIONSHIP BETWEEN DIABETES MELLITUS RISK FACTORSTHAT CAN BE CHANGED WITH THE INCIDENCE OF TYPE 2 DM AT THE PORIAHA HEALTH CENTER 2021 - Leli Desi Uli Basana; Crishartanto Simanungkalit; Ririn Manalu (Institute of Computer Science (IOCS), 2022)
Diabetes mellitus (DM) is a chronic metabolic disorder caused by the pancreas not producing enough insulin or the body not being able to use the insulin it produces effectively. Diabetes will usually appear when you have entered the vulnerable age of 45 years who are overweight, so that the insulin in the body does not respond. The purpose of this study was to determine the relationship between modifiable risk factors for DM and the incidence of type 2 diabetes at the Janti Public Health Center, Malang. The research design used is a correlational method with a cross sectional approach. Collecting data in this study using questionnaires and medical records with the target respondents, namely patients in the working area of the Janti Health Center aged 45 years. There is a significant relationship between BMI, physical activity, hypertension, dyslipidemia, unhealthy diet and prediabetes with the incidence of type 2 DM at the Janti Health Center. The P values yield the order (0.000; 0.000; 0.000; 0.020; 0.002; 0.000 < 0.05). while the variables of central obesity and smoking with the incidence of type 2 DM did not find a significant relationship.